2013
DOI: 10.4103/1817-1745.123694
|View full text |Cite
|
Sign up to set email alerts
|

Pilomyxoid astrocytoma with high proliferation index

Abstract: Pilomyxoid astrocytomas is an uncommon aggressive piloid neoplasm, closely related to pilocytic astrocytomas and typically presents in the very young but can occur in older children and rarely in adults. A 12-years-old male presented with focal seizures, headache and vomiting of 10 days duration. Computed tomogram showed a hypo- to hyperdense and peripherally enhancing, solid-cystic lesion in the left temporal lobe. Histopathological examination revealed a characteristic tumor composed of bipolar cells arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
(11 reference statements)
0
3
1
Order By: Relevance
“…It is notable that mitosis-related genes were overexpressed in PMAs versus PAs despite the known overlap between the rates in these two entities (23). The MIB-1 rates for pure PMAs in our study were not out of range of previously-reported levels (8, 12), and thus our study cohort was not skewed by cases that were exceptionally proliferative, although such cases have been reported (21). Possibly the microarray better detects modest differences in cell cycling between PMAs and PAs than does manual MIB-1 counts.…”
Section: Discussioncontrasting
confidence: 42%
“…It is notable that mitosis-related genes were overexpressed in PMAs versus PAs despite the known overlap between the rates in these two entities (23). The MIB-1 rates for pure PMAs in our study were not out of range of previously-reported levels (8, 12), and thus our study cohort was not skewed by cases that were exceptionally proliferative, although such cases have been reported (21). Possibly the microarray better detects modest differences in cell cycling between PMAs and PAs than does manual MIB-1 counts.…”
Section: Discussioncontrasting
confidence: 42%
“…4,6 However, cases have been identified across a broad age range, even among adults. 8 Clinical presentations vary and include developmental delay, failure to thrive, vomiting, feeding difficulties, and generalized weakness. 6 In infants, the initial clinical manifestations can be more subtle, such as increased head size or bulging fontanelle from increased intracranial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…9 The reported frequency of central necrosis varies; some authors believe it to be rare, while a large review of cases noted necrosis in nearly one-third of tumors. 8,11 Peritumoral edema is infrequently seen. 12 PMAs tend to be devoid of calcifications and do not demonstrate reduced diffusivity, helping distinguish them from craniopharyngiomas and germinomas, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the majority of published case reports, patients had received previous radiotherapy. 4 , 9 , 11 , 12 Therefore, this therapy has been considered a key factor for malignant changes, despite there being no available information about cumulative incidence, risk factors, and molecular abnormalities. 7 Malignant transformation without previous radiotherapy has also been reported but occasionally in a pediatric age and in locations other than the cerebellum.…”
Section: Discussionmentioning
confidence: 99%